¿Asturias, Covadonga, Pelayo? Asturias, Covadonga, Pelayo? - Chalmeta Gendrón, Pedro (Aragón en la Edad Media, 2025)
La trascendencia atribuida tradicionalmente al ‘constructo Pelayo-Covadonga’ me incitó a examinar la presunta historicidad de dicho evento. Para ello se ha partido del análisis de los datos aportados por las propias crónicas asturianas, contrastándolos con los de la única fuente coetánea (Crónica del 754), y cotejarlos finalmente con la tardía versión de las fuentes árabes, Crónica de San Juan de la Peña y Libro de San Voto. De paso, obligó a afinar el significado geopolítico de Galicia, resultando que aquel sonado encuentro bien podría no haber tenido lugar en Asturias… Palabras clave: Asturias, Covadonga, Pelayo, crónicas asturianas, fuentes árabes, siglo VIII. Transcendancy traditionally attributed to the ‘construct Pelayo-Covadonga’ push me to re-examinate the supposed historicity of that event. For this purpose, we started from the analysis of the informations’ accuracy given by the Asturian Chronicles, checking them with the only contemporary source (Chronicle of 754), before starting to collate them finally with the late version given by the Arabic sources, Crónica de San Juan de la Peña y Libro de San Voto. Analysis that deals with a more accurate understanding of the geo-political meaning of Galicia, and reaching a new conclusion: it seems that the famous battle had not to be located in Asturias... Key words: Asturias, Covadonga, Pelayo, Asturian chronicles, Arabic sources, 8th century.